Analisis Flyrock Untuk Mengurangi Radius Aman Alat Pada Peledakan Batuan Andesit Di Kecamatan Margaasih, Kabupaten Bandung, Provinsi Jawa Barat - Shilvyanora aprilia rande; Ardila Yulianti (PROMINE, 2021)
Bandung regency known to have had to scatter material which be potential sources of revenue of them are material andesit mining sand and also .Research objectives is measuring the estimation of the distance the throw rocks due to maximum blasting , restudying in the determination of a radius of secure at blasting activities by counting the radius of safe to an instrument based on a theory that is compared with actual that had broken out and get constant k in signification fly rock according to alan b.richards and adrian j.moore to adjust to those of the rocks and stemming used .The research was done by counting the throw of maximum rock theoretically menutut alan b .Ricahrds and adrian j .Moore coupled with the observation actual fly rock in the field with the observation use video and the naked eye .Trial done by moving a radius of safe instrument less than 300 m. From the trial data, it is obtained that the maximum throw of the actual rock and the prediction with the theoretical calculation is in accordance with the recommendation of Adrian J. Moore and Alan B. Richard, so the radius to secure the tool is at least 2 times that of the actual throw. With the provision of using stemming, the safe radius for blasting is reduced to 200 m.